An Objective Method to Determine the Electrically Evoked Stapedius Reflex Threshold During Cochlea Implantation. Issue 1 (January 2018) - Weiss, Bernhard G.; Söchting, Friederike; Bertlich, Mattis; Busch, Martin; Blum, Jenny; Ihler, Friedrich; Canis, Martin
Abstract : Objective: In cochlea implantation, assessment of the electrically evoked stapedius reflex threshold (eSRT) provides information for postoperative adjustment of the speech processor. This is used to prevent undesired overstimulation. To this day, the reflex is visually identified by the surgeon. However, this method may be prone to error due to ventilation-associated situs excursions, blinking, or other distractions. Therefore, the aim of this study was to establish an objective and automatized method to determine the eSRT. Methods: Video material documenting the intraoperative measurements was analyzed offline applying a tracking software to quantify stapes head movements. Moreover, a computer program (TrackerAnalyzer) was developed to detect reflex associated movements automatically. Results: Reflex responses seen visually by the surgeon compared with visual registration on the video material postoperatively and to results of the automatized method with TrackerAnalyzer showed a high inter-rater agreement (Cohen's kappa coefficient = 0.47–0.59). 82% of events in which the TrackerAnalyzer registered reflexes that were not seen by the surgeon had values close but lower to the intraoperatively determined eSRT (mean −1.02 current units). Conclusion: We demonstrated the feasibility of an objective and automatized method to determine electrically evoked stapedius reflex thresholds in cochlea implantation. Abstract : Supplemental Digital Content is available in the text